Potential diagnostic markers and therapeutic targets for obstructive sleep apnea with comorbid depression based on bioinformatics analysis - Lu, Yinfei; Tang, Zao; Zhou, Xiangyu; Lin, Wanting; Guo, Xiao (Frontiers in Genetics, 2025)
BackgroundObstructive sleep apnea (OSA) and major depressive disorder (MDD) impose substantial quality-of-life burdens and socioeconomic costs. Growing evidence indicates bidirectional disease interactions that exacerbate clinical outcomes. This study identifies diagnostic biomarkers and explores therapeutic targets underlying OSA-MDD comorbidity.MethodsWe analyzed OSA/MDD-specific differentially expressed genes (DEGs) from Gene Expression Omnibus (GEO) datasets. Weighted gene co-expression network analysis (WGCNA) identified co-expressed modules. Protein-protein interaction (PPI) networks derived key genes via STRING. Diagnostic markers were established through dual-algorithm screening, with immune associations and therapeutic potential assessed. Finally, in vitro validation confirmed key findings.ResultsWe identified 77 comorbid OSA-MDD DEGs. Integrated WGCNA-PPI analysis revealed eight key hub genes. LASSO regression nominated three diagnostic markers, including CD74 (CD74 molecule), RPL26L1 (ribosomal protein L26 like 1), and MRPL9 (mitochondrial ribosomal protein L9). MRPL9 was excluded for low diagnostic value for OSA and MDD. CD74 and RPL26L1 markers correlated with immune cell infiltration in OSA and MDD. In vitro, intermittent hypoxia significantly upregulated CD74 and RPL26L1 in microglia versus normoxia controls.ConclusionCD74 and RPL26L1 represent mechanistically grounded diagnostic biomarkers and therapeutic targets for OSA-MDD comorbidity. Shared pathways offer novel intervention opportunities for both conditions.